Pemeliharaan Anak Setelah Perceraian - Budiman, Fernanda Akbar; Salam, Abdul (Legal Spirit, 2024)
Child care involves parents, namely father and mother, as parties who have responsibility for their children. As time goes by, sometimes disputes occur between husband and wife which result in divorce. The purpose of this writing is to find out about child maintenance after divorce according to statutory regulations. Child care after divorce is regulated in Law Number 35 of 2014 concerning Child Protection and Law Number 1 of 1974 concerning Marriage. Child maintenance after marriage in the case study of Decision Number 395/Pdt.G/2021/PN Jkt.Utr. It started with the Plaintiff (Wife) and the Defendant (Husband) who divorced, they had two sons, namely Brother A and Brother B. In this case there has been a divorce, then the parents, either father or mother, are obliged to provide maintenance for their children. until they are adults or able to stand on their own. These children's rights are supported by Article 14 of the Child Protection Law where children have the right to meet directly or have personal contact with their parents, children have the right to receive care, maintenance, education and protection for the growth and development process from their parents according to their abilities, talents and interests, the right to receive living expenses from both parents, and the right to obtain other children's rights. So that the two children of the Plaintiff and Defendant are entitled to receive maintenance in the form of a place to live with the mother because she is the closest person to the child and receives support and education from father to adult.